China dreams : 20 visions of the future - Callahan, William A. (Oxford University Press, 2013)
After celebrating their country's three decades of fantastic economic success, many Chinese are now asking,'What comes next?'How can China convert its growing economic power into political and cultural influence around the globe? William A. Callahan's China Dreams gives voice to China's many different futures by exploring the grand aspirations and deep anxieties of a broad group of public intellectuals. Stepping outside the narrow politics of officials vs. dissidents, Callahan examines what a third group - 'citizen intellectuals' - think about China's future. China Dreams eavesdrops on fascinating conversations between officials, scholars, soldiers, bloggers, novelists, film-makers and artists to see how they describe China's different political, strategic, economic, social and cultural futures. Callahan also examines how the PRC's new generation of twenty- and thirty-somethings is creatively questioning'The China Model'of economic development. The personal stories of these citizen intellectuals illustrate China's zeitgeist and a complicated mix of hopes and fears about'The Chinese Century,'providing a clearer sense of how the PRC's dramatic economic and cultural transitions will affect the rest of the world. China Dreams explores the transnational connections between American and Chinese people, providing a new approach to Sino-American relations. While many assume that 21st century global politics will be a battle of Confucian China vs. the democratic west, Callahan weaves Chinese and American ideals together to describe a new'Chimerican dream.'